2019
DOI: 10.12688/gatesopenres.12968.1
|View full text |Cite
|
Sign up to set email alerts
|

Access to contraceptives for adolescents in northern Nigeria – a cross-sectional study from three secondary health facilities in Kaduna metropolis, Kaduna

Abstract: Background: In 2015, the United Nations Development Programme (UNDP) noted that countries will need to meet the increasing demand for contraceptives by the over 600 million 15- to 19-year-olds around the world. Although the unmet need for contraception for Women of Child Bearing Age (WCBA) in Nigeria is 12.7%, the value is higher (35.3%) among adolescents aged 15 – 19 years. Additionally, the unmet need for family planning (FP) among WCBA in Kaduna state is 5.8%, with 33.3% of women aged 20-24 years in Kaduna … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
(3 reference statements)
0
6
1
Order By: Relevance
“…With low contraceptive utilization, and with Uganda having some of the highest adolescent fertility rates in the region, these findings imply that a lot has to be done to ensure increased access and utilization of contraceptives as one of the ways of reducing teenage pregnancies and the associated morbidity and mortality if we are to meet the SDG targets as a country. Our study in comparison to other studies showed that contraceptive utilization in Uganda is lower than that of Kenya, Rwanda, Tanzania, Europe, Latin America and United States of America [1,5,16,[27][28][29] and higher than that in Nigeria [30]. The higher prevalence in Kenya can be attributed to the increased funding of policies and interventions being implemented by the Kenyan government compared to Uganda [1,16].…”
Section: Discussioncontrasting
confidence: 53%
“…With low contraceptive utilization, and with Uganda having some of the highest adolescent fertility rates in the region, these findings imply that a lot has to be done to ensure increased access and utilization of contraceptives as one of the ways of reducing teenage pregnancies and the associated morbidity and mortality if we are to meet the SDG targets as a country. Our study in comparison to other studies showed that contraceptive utilization in Uganda is lower than that of Kenya, Rwanda, Tanzania, Europe, Latin America and United States of America [1,5,16,[27][28][29] and higher than that in Nigeria [30]. The higher prevalence in Kenya can be attributed to the increased funding of policies and interventions being implemented by the Kenyan government compared to Uganda [1,16].…”
Section: Discussioncontrasting
confidence: 53%
“…Some studies have shown that uptake of family planning among adolescents is on the increase compared with uptake among older women [19], [20]. Low utilization of family planning was reported in northern Nigeria especially among adolescents [3], factors such as religion, culture and desire for large family could have been responsible for the low utilization. There are other reasons why there is low utilization of family planning among adolescents in Nigeria; most adolescents would not want to put themselves through the challenge of being stigmatized in health facilities where they can go to for easy access to family planning services, some parents find it difficult to give their children sex education because talking about sex openly is tagged to be a taboo in most communities in Nigeria and this is fueled by cultures, traditions and religion.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these adolescents end up getting married early, and most of them are not exposed to the use of contraceptive due to poor education and information on the availability and importance of family planning. Some have poor attitude to accessing healthcare in health facilities due to shame of being pregnant early [3]. According to Nigeria Demographic and Health Survey [4], 23% of adolescents aged 15 -19years have already begun childbearing and about 32% of women 20 -49 have had a birth at the age of 18years.…”
Section: Introductionmentioning
confidence: 99%
“…22 Adolescent girls in Nigeria have unfettered access to all the mix of contraceptives as over-the-counter (non-prescription) pharmaceuticals. [23][24][25] Although breast cancer risk accumulates throughout a woman's life, research suggests that the time between menarche and first pregnancy may be particularly critical. 26 There are also concerns on ethical issues in the introduction of underage girls to contraceptives.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Various political, economic, and sociocultural factors restrict the delivery of information and services, embarrassment, overloaded clinics (multiplicity of clients), long waiting time, absence of personalized services and possibility of any opportunity of dialogue with the providers, concern about confidentiality (fear of identification and parents/teachers being informed), socio-cultural norms about sex and adolescent use of contraceptives, and where family planning services are offered, low-risk perception and actual or perceived cost of contraceptives. 122,124,128,133,134 Thus special efforts are needed to respond effectively to adolescent needs in public FP facilities.…”
Section: Barriers To Adolescent Contraceptive Uptakementioning
confidence: 99%